2015
DOI: 10.1016/j.yebeh.2015.06.024
|View full text |Cite
|
Sign up to set email alerts
|

Complex syntax in the isolated right hemisphere: Receptive grammatical abilities after cerebral hemispherectomy

Abstract: Objectives: In this study, we explored the syntactic competence of the right hemisphere (RH) after left cerebral hemispherectomy, on the premise that it (syntactic competence) is known to be one of the most strongly leftlateralized language functions. As basic syntactic development for individuals in this subject pool has already been extensively explored, we focused instead on the investigation of complex syntactic constructions that are normally acquired later in childhood, i.e., between 7 and 9 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Maximal professional intervention documented postsurgically was weekly sessions with a speech‐language pathologist (SLP) during the academic year. All participants in the prenatal infarct group had age‐appropriate speech and comprehension of language at testing, based on data using previously published assessments, although detailed examination revealed subtle syntactic deficits in some of them . All families reported no history of left‐handedness in the family, and each participant's use of his/her left hand from early on was probably due to the hemiparesis associated with stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Maximal professional intervention documented postsurgically was weekly sessions with a speech‐language pathologist (SLP) during the academic year. All participants in the prenatal infarct group had age‐appropriate speech and comprehension of language at testing, based on data using previously published assessments, although detailed examination revealed subtle syntactic deficits in some of them . All families reported no history of left‐handedness in the family, and each participant's use of his/her left hand from early on was probably due to the hemiparesis associated with stroke.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging studies have shown that children with large left hemispheric lesions who undergo early hemispherotomy will remap language to the intact right hemisphere in a thorough enough manner to have complete acquisition of syntax and grammatical construction. (53) Language recovery has been reported to be more rapid and complete in younger children after hemispherotomy(58), suggesting a critical window for remodeling after surgery that would support an “earlier is better” approach to large resections in terms of language recovery. A recent analysis of language reorganization after acquired unilateral insults during childhood supports this notion, suggesting more complete and functional reorganization to the non-dominant hemisphere after acute lesions occurring before, as opposed to after, age 5 years.…”
Section: Etiology Of Language Dysfunctionmentioning
confidence: 99%
“…Lastly, phrases and sentences differed most strongly over right-posterior parietal cortex, which is broadly consistent with previous research on speech comprehension. Functional Magnetic Resonance Imaging (fMRI) studies implicate the posterior right hemisphere in processing syntactic structure (de Bode, Smets, Mathern, & Dubinsky, 2015;Grodzinsky, 2000;Grodzinsky & Friederici, 2006;Maess, Koelsch, Gunter, & Friederici, 2001). Neurophysiological research also suggests the involvement of right hemisphere in extraction of slow timescale information extraction (Abrams, Nicol, Zecker, & Kraus, 2008;Giraud et al, 2007;Morillon, Liégeois-Chauvel, Arnal, Bénar, & Giraud, 2012;Poeppel, 2003).…”
Section: Phase Connectivitymentioning
confidence: 99%